2019
DOI: 10.1186/s12944-019-1169-2
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, resistin and visfatin as useful predictors of gestational diabetes mellitus

Abstract: BackgroundLipids and adipokines including leptin, resistin and visfatin play various roles in the pathophysiology of Gestational Diabetes Mellitus (GDM). This study was aimed at determining whether serum leptin, resistin and visfatin are significantly altered during the first trimester of pregnancies that subsequently develop GDM and whether such changes are useful in predicting the disease.MethodsThis was a case-case control study which compared first trimester biochemical and anthropometric parameters in 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 41 publications
5
35
0
1
Order By: Relevance
“…Thus, there will be increased omentin levels in early pregnancy, and omentin clearance during the later stages of pregnancy. Second, omentin may be increased in the second trimester of pregnancy because of increased fat accretion or decreased secretion from maternal adipose tissue [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there will be increased omentin levels in early pregnancy, and omentin clearance during the later stages of pregnancy. Second, omentin may be increased in the second trimester of pregnancy because of increased fat accretion or decreased secretion from maternal adipose tissue [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, visfatin appears to be involved in glucose metabolism regulation and IR, suggesting its role in GDM pathogenesis 59 . Research reports have shown increased levels of circulating visfatin in pregnancies complicated with GDM 36,54,58,61,79 . The reason why women with increased BMI are at greater risk of developing GDM is related to an increase in IR.…”
Section: Visfatin and Obesity‐related Pregnancy Complicationsmentioning
confidence: 99%
“…Nowadays, many specialists focus their eyes on the role of adipokines, which contributes to the metabolic abnormalities in the mother. Some study found statistical difference in adiponectin and zinc-a2-glycoprotein between GDM patients and normal pregnant women 6,7 . ZAG is a new type of adipocytokine secreted by adipocytes, which exists in human plasma and other various body uids including sweat, milk and urine 8,9 .…”
Section: Introductionmentioning
confidence: 99%